2015
DOI: 10.1002/lno.10108
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence‐based source tracking of organic sediment in restored and unrestored urban streams

Abstract: Fine sediment is a leading cause of impairment of waterways, but its dynamics are generally poorly understood. Most fingerprinting studies focus on the mineral component of fine sediment, yet the organic fraction has distinct effects on ecosystem processes. Here we employed a novel combination of fluorescence spectroscopy and end‐member mixing analysis (EMMA) to distinguish between sources of particulate organic material (POM) in streams with and without restoration structures, situated within urban watersheds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 146 publications
(143 reference statements)
5
23
0
Order By: Relevance
“…Although there was increased solute and particle exchange with storage zones in the restored stream (greater V W , V P , and V′ h , Table ), there was not increased net retention of fine particulate matter (lower V P‐NET and similar V′ h,P , Table ). Both local‐scale and reach‐scale results support the conclusion from Larsen et al () that fine particulate matter is more poorly retained in the hyporheic zone of the restored stream than in the unrestored stream. Limited hyporheic retention of fine particles, including particulate organic carbon and microbes, may help to explain why installation of cross vanes does not necessarily lead to increased nutrient uptake (Zimmer & Lautz, ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Although there was increased solute and particle exchange with storage zones in the restored stream (greater V W , V P , and V′ h , Table ), there was not increased net retention of fine particulate matter (lower V P‐NET and similar V′ h,P , Table ). Both local‐scale and reach‐scale results support the conclusion from Larsen et al () that fine particulate matter is more poorly retained in the hyporheic zone of the restored stream than in the unrestored stream. Limited hyporheic retention of fine particles, including particulate organic carbon and microbes, may help to explain why installation of cross vanes does not necessarily lead to increased nutrient uptake (Zimmer & Lautz, ).…”
Section: Resultssupporting
confidence: 83%
“…Previous research within the Chesapeake Bay watershed has demonstrated that retention of total suspended sediment within watersheds is greater than export, but restoration efforts have not significantly reduced suspended sediment loads in small‐order streams (Filosofo et al, ). In fact, a restored stream within the Chesapeake Bay watershed was observed to have higher particulate organic matter export during storms compared to an unrestored stream, with contributions from the bed making up a lower proportion of the suspended sediment pool (Larsen et al, ). Detailed quantification of fine particle transport and retention is needed to improve understanding of how restoration structures change fine particle dynamics and overall particle accumulation and efflux in restored streams.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating DOM chemistry using fluorescence spectroscopy in headwater catchments during saturation permits us to infer hydrologic connectivity between the terrestrial landscape and the stream by using DOM composition as a tracer of hydrochemistry and streamflow generation sources [ Vidon et al ., ; Miller and McKnight , ; Nguyen et al ., ; Inamdar et al ., ; Larsen et al ., ]. Our data demonstrated qualitative and quantitative evidence of a relatively large contribution of soil water sources to the stream during snowmelt.…”
Section: Discussionmentioning
confidence: 99%
“…We followed methods similar to Larsen et al . [] to determine which fluorescent components were potentially conservative in our study. We created biariate mixing diagrams with all possible combinations of our measured fluorescent components.…”
Section: Methodsmentioning
confidence: 99%
“…Fine particles (<100 μm) are important to a broad range of key stream ecosystem processes, including carbon cycling (Battin et al, 2003;Larsen et al, 2015) and reactivity (i.e., metabolic activity and nutrient uptake), but excess particles can clog the streambed sediment matrix and alter streambed oxygen dynamics (Briggs et al, 2015;Hartwig & Borchardt, 2014). Both organic and mineral fine particles provide a colonizable surface area for bacteria (Mendoza-Lera et al, 2016) and, therefore, strongly influence pathogen transmission in streams (Bradford et al, 2013;Drummond et al, 2018).…”
Section: Introductionmentioning
confidence: 99%